2015
DOI: 10.1113/jp271626
|View full text |Cite
|
Sign up to set email alerts
|

Direct effect of chronic hypoxia in suppressing large conductance Ca2+‐activated K+ channel activity in ovine uterine arteries via increasing oxidative stress

Abstract: Key pointsr Chronic hypoxia has a direct effect in down-regulating the BK Ca channel β1 subunit and inhibiting the BK Ca channel activity in uterine arteries of pregnant sheep.r Oxidative stress plays a causal role in hypoxia-mediated suppression of BK Ca channel function. r The steroid hormone-induced effect on BK Ca channels is a target of hypoxia-mediated oxidative stress.r Inhibition of oxidative stress ameliorates the adverse effect of hypoxia both ex vivo and in vivo in pregnant sheep exposed to long-ter… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
32
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 25 publications
(34 citation statements)
references
References 70 publications
(209 reference statements)
2
32
0
Order By: Relevance
“…In addition, the presence of accessory subunits may contribute to BK dependence on redox. Recently, Hu and colleagues reported that oxidative stress acts to directly decrease BK current density in sheep uterine arteries during chronic hypoxia by downregulating its β1 accessory subunit (Hu et al, 2015). Another β-subunit of BK channel, β3, brings redox-dependent gates that block ion permeation (Zeng et al, 2003).…”
Section: Oxidation Of K + Channelsmentioning
confidence: 99%
“…In addition, the presence of accessory subunits may contribute to BK dependence on redox. Recently, Hu and colleagues reported that oxidative stress acts to directly decrease BK current density in sheep uterine arteries during chronic hypoxia by downregulating its β1 accessory subunit (Hu et al, 2015). Another β-subunit of BK channel, β3, brings redox-dependent gates that block ion permeation (Zeng et al, 2003).…”
Section: Oxidation Of K + Channelsmentioning
confidence: 99%
“…For the first time, the current study explored the effect of silymarin plus ® in the uterine wash in comparing with Amikacin+ Ciprofloxacin. The current results revealed that both silymarin plus ® alone or in combination with Amikacin+ Ciprofloxacin improved mare conception and pregnancy rates .These results might be due to the powerful antioxidant capability of silymarin plus ® due to its components that represented in Silymarin, vitamin E and C, Selenium Hu et al, 2016). The association between ROS and various gynecologic and obstetric conditions related to infertility suggests a potential role for oral antioxidant supplementation.…”
mentioning
confidence: 54%
“…Acetylcysteine (NAC) is the N-acetyl stable derivative of L-cysteine; a precursor of glutathione (Gayatri et al, 2010 andHu et al, 2016), which functions as an ROS scavenger through increasing intracellular glutathione formation and its thiol-disulfide exchange activity (Zafarullah et al 2003). Furthermore, NAC has anti-inflammatory and mucolytic effects (Conesa et al, 2001 andSehirli et al, 2003;Ocal et al, 2004 andGayatri et al, 2010).…”
mentioning
confidence: 99%
“…; Rosenfeld and Roy ), and oxidative stress suppresses this BK activation (Hu et al. ). Any gene dosage effects from the (+/−) Kcnma1 dams likely would influence blood flow to all of the fetuses equally.…”
Section: Discussionmentioning
confidence: 99%
“…In contrast, fetuses adjacent to hypoperfusion mutant fetuses exhibited increased maternal blood volume in their placenta indicating an advantage for growth. Increases in blood flow to the placenta occur through opening of BK channels that dilate uterine smooth muscle cells (Rosenfeld et al 2009;Rosenfeld and Roy 2012), and oxidative stress suppresses this BK activation (Hu et al 2016). Any gene dosage effects from the (+/À)Kcnma1 dams likely would influence blood flow to all of the fetuses equally.…”
Section: Influences Of Bk During the Prenatal Periodmentioning
confidence: 99%